2021
DOI: 10.21776/ub.jam.2021.019.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy Challenges: The Case of Filipino Public-School Teachers

Abstract: This study analyzed the Philippine public school teachers' financial literacy challenges. The data and results were gathered through online survey questionnaires and focused group discussions conducted in the school year 2019-2020. Twelve participants contributed to the FGD, while a total of 325 teacher respondents answered the online survey questionnaires. The results showed that the majority of the public-school teachers are struggling financially. That results in a controlled and limited financial lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This suggest that the teachers occasionally experienced difficulty in their finances. This conforms to the findings of the study conducted by Casingal and Ancho (2021) in their study showed that the majority of the public-school teachers are struggling financially. More-over, teachers unconsciously practice informal debt, which causes uncontrolled debt.…”
Section: Resultssupporting
confidence: 91%
“…This suggest that the teachers occasionally experienced difficulty in their finances. This conforms to the findings of the study conducted by Casingal and Ancho (2021) in their study showed that the majority of the public-school teachers are struggling financially. More-over, teachers unconsciously practice informal debt, which causes uncontrolled debt.…”
Section: Resultssupporting
confidence: 91%
“…The absence of financial literacy programs in schools has led to poor financial knowledge, decision-making skills, and understanding. Schools or the government must develop and provide an effective, better, and well-planned financial literacy program for teachers (Casingal & Ancho, 2021). Teachers who are also members of a household will have concerns in relation to economy.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, public school teachers of the Philippines continue to be indebted to creditors which also has an indirect impact to their performance. Majority of schoolteachers are struggling with their finances leading to a constrained life [6].…”
Section: Since I Am a Government Employee I Can Say That I Am Financi...mentioning
confidence: 99%
“…Usually, they end up being engaged in formal and even in informal borrowing [4,5]. Unfortunately, teachers who are submerged to informal debt usually end up economically challenged due to the need to pay off higher interest rates which results to more borrowing [6]. It is therefore important to underscore the need to strive for financial stability achieved through literacy.…”
Section: Introductionmentioning
confidence: 99%